2018
DOI: 10.3171/2017.2.jns161770
|View full text |Cite
|
Sign up to set email alerts
|

Transitional care services: a quality and safety process improvement program in neurosurgery

Abstract: OBJECTIVE Readmissions increasingly serve as a metric of hospital performance, inviting quality improvement initiatives in both medicine and surgery. However, few readmission reduction programs have targeted surgical patient populations. The objective of this study was to establish a transitional care program (TCP) with the goal of decreasing length of stay (LOS), improving discharge efficiency, and reducing readmissions of neurosurgical patients by optimizing patient education and postdischarge surveillance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 51 publications
(65 reference statements)
0
27
0
4
Order By: Relevance
“…In the current health-care climate, multiple metrics have been evaluated in an effort to improve patient outcomes in a most cost-efficient manner. 13 , 14 Postsurgical length of inpatient hospital stay has become a commonly utilized metric in this regard. 13 , 14 , 16 18 The rise in implementation of enhanced recovery pathways after autologous breast reconstruction has mirrored the effort to reduce postoperative LOS and associated costs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current health-care climate, multiple metrics have been evaluated in an effort to improve patient outcomes in a most cost-efficient manner. 13 , 14 Postsurgical length of inpatient hospital stay has become a commonly utilized metric in this regard. 13 , 14 , 16 18 The rise in implementation of enhanced recovery pathways after autologous breast reconstruction has mirrored the effort to reduce postoperative LOS and associated costs.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 14 Postsurgical length of inpatient hospital stay has become a commonly utilized metric in this regard. 13 , 14 , 16 18 The rise in implementation of enhanced recovery pathways after autologous breast reconstruction has mirrored the effort to reduce postoperative LOS and associated costs. 13 , 14 , 16 19 , 21 For instance, Afonso et al demonstrated significantly reduced length of hospital stay after autologous breast reconstruction with implementation of an enhanced recovery pathway comprised of reducing opioid-centered pain management, regional abdominal blocks, and goal-directed fluid therapy, among other changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preventing readmission rests on improved discharge education and optimized outpatient follow-up. Specifically, discharge education is one of the interventions that has been shown to help reduce overall unplanned hospital readmissions at 30 and 90 days [1] for a variety of medical conditions, which include stroke [[2], [3], [4], [5], [6]], congestive heart failure, and diabetes [7,8]. There is inherent value in training future physicians how to provide patient-centered discharge education.…”
Section: Introductionmentioning
confidence: 99%
“…The time of discharge is chaotic and the patients experience an overwhelming amount of new information at the time. Robertson et al (2018) found that SSI (surgical site infection) rates may be reduced though discharge planning strategies and targeted patient education. If the patient was inadequately engaged or lacked comprehension, it affected the compliance and recognition of complications, placing them at risk for readmission.…”
Section: Background and Significancementioning
confidence: 99%